Principal Performance and Teacher Work Discipline on Learning Quality at Kindergarten in Aceh Besar - Yuliana, Elly; AR, Murniati; Usman, Nasir (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Performance can be defined as work achievement or execution, as well as the consequence of a work presentation. One of the variables influencing the performance of school principals and instructors is their ability to carry out their separate jobs. This study aims to determine: the performance of school principals, the implementation of teacher work discipline, an assessment of the impact of school principal performance and teacher work discipline on the quality of Kindergarten in Aceh Besar. This study employs a qualitative approach and descriptive approaches. The subjects of this study are principals and teachers from Aceh Besar Regency. Data collection methods include observation, interviews, and documentary studies. Data analysis techniques include data reduction, data display, and making conclusions. The findings of this investigation are as follows: 1) the performance of school principals in Aceh Besar significantly influences the quality of education in schools, as school principals perform their duties and functions effectively, ensuring that every activity is carried out in a directed and structured manner; 2) teacher work discipline in carrying out their duties and obligations significantly affects the quality of Kindergarten in Aceh Besar; and 3) there is an influence of the performance of school.